2005
DOI: 10.1007/s00430-005-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the protective immune response against streptococcal superantigens in populations of different ethnicity

Abstract: Superantigens (SAgs) from group A streptococcus (GAS) are potent T cell mitogens, and have been suggested to play a role in severe streptococcal disease. Neutralizing antibodies protect against SAg-mediated disease and their levels should therefore be inversely related to severe streptococcal infection. Neutralizing anti-SAg titers in patients with severe GAS infection and patients without disease were compared in two separate groups. The first group comprised patients with invasive GAS disease from New Zealan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The additional association between certain emm types and the presence of superantigen genes [28,29] might link HLA class II haplotypes and emm types indirectly. This would explain the worldwide regional variations in group A Streptococcus and associated superantigen gene profiles as well as in the emm types [33,50].…”
Section: Discussionmentioning
confidence: 97%
“…The additional association between certain emm types and the presence of superantigen genes [28,29] might link HLA class II haplotypes and emm types indirectly. This would explain the worldwide regional variations in group A Streptococcus and associated superantigen gene profiles as well as in the emm types [33,50].…”
Section: Discussionmentioning
confidence: 97%
“…Higher responses were found against: Helicobacter pylori in non-Japanese Brazilians than Japanese Brazilians [17]; Streptococcus pyogenes superantigen in Polynesian than New Zealand Europeans [18]; Plasmodium falciparum in Fulani than sympatric ethnic groups in Burkina Faso [19]; P. falciparum in Austro-Asiatic than Tibeto-Burman groups in north-east India [20]. Jensen et al [21] reported comparatively higher anti- Plasmodium titres in subjects from Flores (Indonesia) than in counterparts from southern Sudan.…”
Section: Discussionmentioning
confidence: 99%
“…Among paediatric patients, preceding varicella‐zoster infection and age of first exposure are associated with invasive disease (Laupland et al ., 2000; Factor et al ., 2005; Yang et al ., 2006). Interestingly, necrotizing fasciitis is relatively uncommon among paediatric patients (Lamagni et al ., 2008).…”
Section: Invasive Infectionsmentioning
confidence: 99%